2014
DOI: 10.1080/00029157.2014.906152
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotizability, Personality Style, and Attachment: An Exploratory Study, Part 1—General Results

Abstract: This article is an exploratory study investigating the relationship between hypnotizability, personality style, and attachment. Data were collected from 99 students by means of the Harvard Group Scale of Hypnotic Susceptibility, Form A; Personality Styles and Disorders Inventory; and Relationship Scale Questionnaire. Results suggest that individual personality styles accounted for a significant amount of variance in hypnotizability in: (a) the whole sample, (b) the securely attached, and (c) the insecurely att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…In particular, it is the only theoretical account of heterogeneity among highly suggestible individuals (Terhune & Cardeña, 2015) and it provides a set of testable predictions for why patients with dissociative disorders exhibit high suggestibility and yet another subset of highly suggestible individuals are characterized by a healthy cognitive profile and a developmental trajectory involving parental encouragement of imagination (Barber, 1999;Carlson & Putnam, 1989; J. R. Hilgard, 1979). The present work provides further corroboration for these pathways and expands upon the proposed mechanisms of this model by highlighting the potential (moderating) roles of anxious and secure attachment, respectively (see also (Peter et al, 2011;Peter et al, 2014)). Elsewhere it has been hypothesized that a secure upbringing involving high quality parenting allows individuals to develop executive control and a reduced predisposition to an orienting system in childhood that relies upon parental intervention, resulting in low or moderate responsiveness to verbal suggestion (Posner & Rothbart, 2011).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In particular, it is the only theoretical account of heterogeneity among highly suggestible individuals (Terhune & Cardeña, 2015) and it provides a set of testable predictions for why patients with dissociative disorders exhibit high suggestibility and yet another subset of highly suggestible individuals are characterized by a healthy cognitive profile and a developmental trajectory involving parental encouragement of imagination (Barber, 1999;Carlson & Putnam, 1989; J. R. Hilgard, 1979). The present work provides further corroboration for these pathways and expands upon the proposed mechanisms of this model by highlighting the potential (moderating) roles of anxious and secure attachment, respectively (see also (Peter et al, 2011;Peter et al, 2014)). Elsewhere it has been hypothesized that a secure upbringing involving high quality parenting allows individuals to develop executive control and a reduced predisposition to an orienting system in childhood that relies upon parental intervention, resulting in low or moderate responsiveness to verbal suggestion (Posner & Rothbart, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…Despite these results, the predictions of the two models have undergone little empirical scrutiny and neither has incorporated the role of insecure attachment styles (e.g., anxious attachment), which are known to mediate or moderate the relationship between trauma and dissociation (Byun et al, 2016;Gušić et al, 2016). Research has also shown that insecure attachment is associated with high hypnotic suggestibility (Peter et al, 2011) or that highly suggestible subtypes, may be characterized by secure or insecure attachment (Peter et al, 2014), thereby warranting the incorporation of attachment as a moderator in both models (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…(We refer to this issue in Table 6 and in the "Discussion" section.) According to many studies including ours (Peter and Böbel, 2020;Peter et al, 2014, Peter et al, 2017, the PSDI is a very well-suited instrument to research personality.…”
Section: Psdi For Personality Stylesmentioning
confidence: 99%
“…For example, using the Minnesota Multiphasic Personality Inventory, 15 one study indicated that people with high hypnotic susceptibility scored higher in depression, masculinity–femininity, and schizophrenia scales than people with low hypnotic susceptibility did, 16 but another study failed to replicate the results. 17 Nevertheless, more recent studies kept showing new evidence that persistence, 18 emotional contagion, 19 and unselfish/self-sacrificing, 20 were linked with hypnotic susceptibility.…”
Section: Introductionmentioning
confidence: 99%